Pelaksanaan Program Bank Sampah sebagai Upaya Pemberdayaan Masyarakat di Dusun Gerdu, Desa Tulungrejo, Kecamatan Bumiaji, Kota Batu - Dhani, Shefia Anggraeni Rama; Nugroho, Rivo (J+PLUS UNESA, 2026)
This study aims to analyze the implementation of the waste bank program as an effort toward community empowerment in RW 06, Gerdu Hamlet, Tulungrejo Village, Bumiaji District, Batu City. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving four informants consisting of waste bank administrators, community members of RW 06, and community leaders in Gerdu Hamlet. The findings revealed that the implementation of the waste bank program was carried out through four main functions, namely motivation, direction, communication, and leadership. The program contributed positively to improving environmental quality, developing community skills and creativity, and strengthening social relationships among residents. However, the implementation of the program has not yet been fully optimal due to uneven community participation, the limited number of active members, and inadequate facilities and infrastructure. Supporting factors for the program’s success include community awareness and concern for the environment. Meanwhile, inhibiting factors include low levels of participation and limited available resources. Therefore, efforts are needed to increase community participation and strengthen facilities and infrastructure support so that the program can be implemented more effectively and sustainably.